PENERAPAN KLASIFIKASI C4.5 DALAM MENINGKATKAN SISTEM PEMBELAJARAN MAHASISWA - P, Dini Rizky Sitorus; Windarto, Agus Perdana; Hartama, Dedy; Damanik, Irfan Sudahri (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
The purpose of this research is to classify the improvement of student learning systems using the C4.5 datamining method. The source of the research data was obtained from the education section of STKOM Tunas Bangsa through interviews and questionnaires to semester 5 students (160 students) in the 2019-2020 academic year study program. The attributes used in the classification of student learning systems include: Teaching System (C1), Teaching Aids (C2), Environment (C3), Infrastructure Facilities (C4) and Assignment (C5). The calculation results mention the attribute Assignment (C5) is the attribute that most influences the improvement of student learning systems. The test was also carried out using the help of Rapidminer software and obtained an accuracy of 95%.Keywords: Datamining, Classification, C4.5, Student Learning, STIKOM Tunas Bangsa